Trajetória da política de educação do/no campo em Paraupebas/Pará de 2005 a 2010 - Silva, Viviane Cardoso (2015)
The education developed in the schools in the rural area, historically, has witnessed the ills and the neglect of the public power. The claims for having schools in the rural area can be observed in surveys such as Andrade (1993) and the question of to think the Brazilian education and the schools in accordance to the social reality has been placed in the agenda since the propositions of the representatives of the new school, with the Manifesto dos Pioneiros da Educação Nova of 1932, though very little progress. After a long period of Civil- Military Dictatorship in Brazil and the opening for the political democratization, the social movements, before silenced, were able to reorganize and others were created, most claiming rights, including land reform, which in its essence also brought the problematic of the developed education in the rural schools of the country. Since to question the rural education to the appearance of the new propositions for an education for the field, whether they be field education or education in the field, we had educational policies created from the 2000's, the result of the debates and concessions in the face of these demands. Since 2001, we are studying this construction process of the policies and their relationship with the field schools, in this sense, arose the interest in analyzing the educational reality in the educational system of the city of Parauapebas/Pará and in Brazil, in the master, to understanding how has developed the rural or field education in this town from 2005 to 2010, in the period when the field research was carried out. As a methodology we chose the qualitative research, using of the following proceedings: bibliographical study, documentary and field research with the collection of materials and images, registering photos on some schools and applying semistructured interviews to five subjects, in exercise, that we believe are relevant to the understanding of our object: Department of education, Coordinator of the rural education Sector, Pedagogical Coordinator of the rural education Sector, representative of the Landless Rural Workers' Movement (MST), representative of the community in which is located the Escola da Pedagogia da Alternância, in addition we collect reports on teachers’ training and in the Escola Jorge Amado, known as Estação Conhecimento created by the Companhia Vale (CV) in one of its properties. As a result we can highlight that although some educational policies for the rural area have been created, still walking at a slow steps as its implementation in this location. The teacher training both in the sense of the valorization and the qualification need to advance, either in the socialization of knowledge historically built by the humanity, or by the historical appropriation of the peasant reality, walking towards the building of a society where the peasant working class and their children have the right to enjoy the benefits provided by the means of production of the society, of their work and of the technological progress. Regarding the schools taken to exemplify the rural schools, it is worth highlighting the importance of the collective construction of the educational process by the school community, as well as, we should observe and supervise private initiatives (such as those undertaken by the Companhia Vale) within the public education, her administration, educational policies and pedagogical training for fighting against privatization processes grounded in the agenda of the capitalist State.